Impact of non governmental organisations (NGOs) in promoting gender equality: a case of Destiny for Women and Youth Empowerment Trust (Dweyt), Harare - Ngadze, Paddington (Midlands State University, 2018)
The study focuses on the impact of NGOs in promoting gender equality based on the Case Study of DWEYT an organization that operates in Budiriro. Gender equality is the view that everyone should receive same treatment and not to be discriminated against based on their gender. The study is examining and exhibiting whether DWEYT operations was a panacea to gender inequities in Budiriro.The study also looks at the nature of DWEYT’s operations and projects carried out in Budiriro as a way of promoting gender equality. This research was based on qualitative research as a method of collecting information from the respondents or interviewees. The researcher used face to face interviews and with the residents of Budiriro and observations and focus group discussions were conducted and this enabled rich and relevant data to be gathered with less bias. The research study confirmed that the impacts of DWEYT can be noticed but there is need to enhance men participation as well for the projects and operations to be more successful. DWEYT’s operations improved the livelihoods of people since women are empowered and able to provide for their families, awareness of gender equality increased low levels of domestic and gender based violence. However patriarch, lack of money lack of endurable awareness campaigns and projects are still impermeable stones that prevent and make the process of achieving gender equality very slow and challenging. The researcher proposes recommendations for the study and these included NGOs, government and the communities to amalgamate and promote gender equality at a high rate. Incorporating men to participate indirectly through teaching them the concept of gender equality and as well as to apply it combined with direct participation of including them to work actively with women in projects and awareness campaigns will promote gender equality.